若a-b/x=b-c/y=c-a/z不等于0则x+y+z=
1个回答
设(a-b)/x=(b-c)/y=(c-a)/z=k,k不=0.
x=(a-b)/k,y=(b-c)/k,z=(c-a)/k
x+y+z=(a-b)/k+(b-c)/k+(c-a)/k
=0/k
=0
相关问题
x/y+z=a,y/z+x=b,z/x+y=c,x+y+z不等于0,求a/1+a+b/1+b+c/1+c
若x/(a+2b+c)=y/(a-c)=z/(a-2b+c),且a,b,c,x,y,z均不为0,求证a/(x+2y+z)
已知a(y-z)+b(z-x)+c(x-y)=0,求证:(x-y)/(a-b)=(y-z)/(b-c)=(z-x)/(c
向量a b c不共面,若(x-y-1)a+(z+y+1)b+(x-z-1)c=0,则x∧2+y∧2+
x-y/a=y-z/b=z-x/c,x,y,z互不相等,求证:a+b+c=0
若[x/2=y7=z5],设A=[y/x+y+z],B=[x+z/y],C=[x+y−z/x],则A,B,C的大小顺序为
已知x.y.z均为实数x+y+z≠0 a=x/y+z b=y/z+x c=z/x+y那么a/a+1+b/b+1+c/c+
已知:a/(z-2y+x)=b/(x-2z+y)=c/(y-2x+z),a+b+c≠0.求证:(a+b)(b+c)(c+
若x/a-b=y/b-c=z/c-a,求x+y+z的值
x-y+z=a x+y-z=b (a,c,b为常数) -x+y+z=c